INFORMATION SITE DEVELOPMENT FOR ZAKAT infak SHODAQO BNI 1946 BAMUIS FOUNDATION USING THE PROGRAM APPLICATION Macromedia Flash MX - Zul Akbar; Ire Puspa W, S. Kom., MMSI (Jurnal Sistem Informasi, 2005)
In  scientific  writing,  the  author  makes  the  site  (website)  by  using  the  programMacromedia Flash MX applications, in order to mensajikan interactive web-animation if theris an animation or design a more vibrant appearance. In discussing this issue be discussed is thway it started to determine the structure of navigation, making navigation maps, create, desiginterface, the formation of elements, combining elements, ActionScript programming, testinup to compile it, so it can run. BAMUIS BNI Foundation in 1946 specifically to develop worprograms for employees or retirees of Bank BNI 1946, the website was made interactive tfacilitate the employee or retiree to get the latest news and information and also the media fosite owners to deliver the news.